"Shouldn't you be collaborative by now?": Supervisory needs, expectations, and satisfaction across the educational trajectory in speech-language pathology. Issue 2 (3rd July 2021) - W. Wolford, George; L. Wolford, Laura; Fissel Brannick, Schea; Scott, Megan; Smith, Rebekah
ABSTRACT: In speech-language pathology, models of supervision suggest supervisors should both adjust their supervisory technique to match learners' needs and provide less-directive support with more experienced learners. This cross-sectional survey design sampled supervisee ( N = 61) needs, expectations, reported supervisor behavior, and satisfaction at different points in their career. Results indicated less of a change in needs and expectations over time than was anticipated. In addition, supervisees reported that supervisors used similar supervisory behaviors regardless of learner experience level. We discuss the implications of these results for supervision methodologies.